The Effect of Feeding Extruded Corn on the Growth Performance of Nursery Pigs Reared under Tropical Conditions - Saichon Lerdsuwon; Seksom Attamangkune (Agriculture and Natural Resources, 2008)
The research was conducted to study the metabolizable energy value of extruded corn and the effect of feeding extruded corn on the growth performance of nursery pigs. Twelve three-way crosses of pigs averaging 18.3 kg BW were used to compare the metabolizable energy value between ground corn and extruded corn. The results indicated that the metabolizable energy value for ground corn and extruded corn was 3497 and 3653 kcal/kg, respectively. The effect of feeding extruded corn on the growth performance was investigated using 192 three-way crosses of pigs averaging 7.8 kg BW. Pigs were randomly separated into three dietary treatments based on three carbohydrate sources (broken rice, ground corn and extruded corn). The pigs were fed with experimental mash diets from 4 to 9 weeks of age. It was found that pigs fed with extruded corn had a poorer average daily weight gain (ADG) and feed conversion ratio (FCR) than pigs fed with ground corn and broken rice (P < 0.05). No significant differences in daily feed intake and mortality were observed among the treatments. Pigs fed with either broken rice or extruded corn were found to have a higher feed cost (P < 0.05) and feed cost per kg body weight gain (P < 0.01) than pigs fed with ground corn.